Rule or feel? The application of implicit and explicit knowledge of Filipino and Korean college students in responding to English tests - Selwyn A. Cruz (Asian Journal of English Language Studies (AJELS), 2013)
The study explores the manifestation of explicit and implicit knowledge among English as a Foreign Language (EFL) and English as a Second Language (ESL) learners of a university in Manila. Using a theoretical framework pioneered by Rod Ellis (2005), the researcher administered to 60 college students a Grammaticality Judgment Test (GJT) designed to elicit their explicit knowledge, and a Free Writing Test (FWT) used to test their implicit knowledge. Using the statistical test of 2x2 factorial design for the GJT and the FWT, the research found that the students used explicit knowledge and implicit knowledge for English tests that require their knowledge of rules and their personal judgment. The study likewise yielded several useful implications for teaching the English grammar in the Philippine context, particularly in the participants’ learning, such as both the EFL and the ESL learners’ ability to access either type of knowledge in language tests and the EFL learners’ ability to progress in their language development in a mixed-ability class.